2014
DOI: 10.1152/ajpgi.00374.2013
|View full text |Cite
|
Sign up to set email alerts
|

Tis7 deletion reduces survival and induces intestinal anastomotic inflammation and obstruction in high-fat diet-fed mice with short bowel syndrome

Abstract: Effective therapies are limited for patients with parenteral nutrition-dependent short bowel syndrome. We previously showed that intestinal expression of the transcriptional coregulator tetradecanoyl phorbol acetate-induced sequence 7 ( tis7) is markedly increased during the adaptive response following massive small bowel resection and tis7 plays a role in normal gut lipid metabolism. Here, we further explore the functional implications of tis7 deletion in intestinal lipid metabolism and the adaptive response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Only recently genuine host factors have been identified that may influence adaptation. Tetradecanoyl phorbol acetate-induced sequence 7 (Tis7) has been characterized to mediate adaptive responses in the intestine and deletion of Tis7 reduces survival in a mouse model of short bowel syndrome [18]. Based on findings in two intestinal transplantation cohorts we have found an increased frequency of nucleotide-binding oligomerization domain-containing protein 2 (NOD2) mutations in patients with short bowel syndrome who did not have Crohn's disease, suggesting that NOD2 plays a role in adaptation [19][20][21].…”
Section: Mechanisms Of Adaptationmentioning
confidence: 97%
“…Only recently genuine host factors have been identified that may influence adaptation. Tetradecanoyl phorbol acetate-induced sequence 7 (Tis7) has been characterized to mediate adaptive responses in the intestine and deletion of Tis7 reduces survival in a mouse model of short bowel syndrome [18]. Based on findings in two intestinal transplantation cohorts we have found an increased frequency of nucleotide-binding oligomerization domain-containing protein 2 (NOD2) mutations in patients with short bowel syndrome who did not have Crohn's disease, suggesting that NOD2 plays a role in adaptation [19][20][21].…”
Section: Mechanisms Of Adaptationmentioning
confidence: 97%
“…The protocols for intestinal resection surgery and for the provision of a liquid high fat diet (42% kcals from fat, Modified, High Fat AIN-93M purified liquid diet 710147, Dyets Inc, Bethlehem PA) for 3 weeks post-op were as described [7]. Briefly, two days prior to surgery mice were acclimated to a liquid control diet nutritionally equivalent to standard rodent chow (described below).…”
Section: Intestinal Resection Surgerymentioning
confidence: 99%
“…On the other hand, we have shown that as a result of impaired intestinal lipid absorption TIS7 knockout mice displayed lower body adiposity 11 . Compared with wild type (WT) littermates, TIS7 knockout mice do not gain weight when chronically fed a HFD and TIS7 deletion results in delayed lipid absorption and altered intestinal and hepatic lipid trafficking, with reduced intestinal TG, cholesterol, and free fatty acid mucosal levels in the jejunum 11,12 . However, at this point, the precise mechanism of TIS7 action in the regulation of lipid absorption and metabolism on the molecular level was unclear.…”
Section: Introductionmentioning
confidence: 99%